Harm, Rights, and Liberty: Towards a Non-Normative Reading of Mill's Liberty Principle - Mulnix (Journal of moral philosophy, 2009)
Abstract Many commentators have argued that Mill's Liberty Principle is most reasonably construed as limiting social interference to cases where an individual's action either harms or increases the probability of harm to others. The convention when it comes to understanding harm seems to be to build into the concept a normative component such that what it means to harm someone is that we have wronged them in some important respect. But such an understanding of harm will vary depending upon which particular moral framework is adopted, and as such, will not achieve the sort of neutrality necessary for the Liberty Principle to be accepted by a liberal society. However, I am unconvinced that we need to appeal to moral concepts in order to fully analyze Mill's Liberty Principle and the ultimate aim of this article is to sketch an account of how his principle could be non-normatively explicated.